KOMPARASI STRATEGI PQ4R DENGAN STRATEGI KOOPERATIF JIGSAWTERHADAP HASIL BELAJAR TEKNOLOGI PENDIDIKAN MAHAMAHASISWA SEMESTER V PROGRAM STUDI PENDIDIKAN AGAMA ISLAM - Junaidi Junaidi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2015)
This article compares PQ4R Strategy, with the Cooperative Strategy Jigsaw, Against Educational Technology Learning Outcomes Studies Program of Islamic Education. The population in this study were all students. This study population is the fourth semester students who are 4 classes of Islamic education courses in Academic Year2014 -2015. The amount of each class of 30 students. Sampling was done by cluster random sampling technique. Results of the research analysis pointed-out that the use of learning strategies PQ4R its better results compared to learning by using Jigsaw learning strategy on learning outcomes Educational Technology student of Islamic Education Semester Va and Vb